Procurement performance in power sector of Banangladesh: a comparative study of a government agency and a public limited company - Siddique, Ishtiak (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.